Productivity growth and micro-level restructuring: Finnish experiences during the turbulent decades - Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2001)
The appearance of productivity-enhancing restructuring at the plant level (the socalled between and net entry effects) has contributed substantially to the acceleration of labour and total factor productivity growth in Finnish manufacturing in the period from the latter part of the 1980s up to the mid-1990s. The recent years have witnessed chilling in these components of aggregate productivity growth. We find evidence that increased export-orientation towards the Western markets and increased R&D intensity have generated the productivity-enhancing restructuring. More specifically, R&D seems to have contributed to aggregate total factor productivity through plant level restructuring with a lag of some 3 to 5 years. The chilling in the between-plant component in recent years can be explained by the fact that while the gap to the international technology frontier is narrowing there are less and less needs and opportunities for productivity improvement through micro-structural adjustment. We have found that microstructural factors of aggregate productivity growth have an important role to play in diminishing productivity and wage dispersion between plants. In the recession years external adjustment through entry and exit and, to a lesser extent, through restructuring among incumbents has improved aggregate productivity performance in some service industries as well. But the recovery period has entailed chill also in many non-manufacturing industries. – productivity ; total factor productivity ; restructuring ; R&D ; competition ; catching up – – Tuottavuutta vahvistavan toimipaikkatason rakennemuutoksen (osuusvaikutuksen) ilmaantuminen on edistänyt merkittävästi työn tuottavuuden ja kokonaistuottavuuden kasvun kiihtymistä Suomen tehdasteollisuudessa 1980-luvun jälkipuoliskolta 1990-luvun puoliväliin. Viime vuosina tämä kasvutekijä on alkanut hyytyä. Saadaan näyttöä siitä, että lisääntynyt vientisuuntautuminen länsimarkkinoille sekä lisääntynyt T&K-intensiteetti ovat lisänneet tuottavuutta vahvistavaa rakennemuutosta. Tarkemmin sanottuna, T&K näyttää vaikuttavan aggregaativiseen kokonaistuottavuuteen osuusvaikutuksen välityksellä noin 3-5 vuoden viiveellä. Osuusvaikutuksen hyytyminen viime vuosina selittyy sillä, että samalla kun teknologiakuilu kansainväliseen teknologian eturintamaan on kaventunut, alati vähemmän on tarvetta ja mahdollisuutta tuottavuuden parannuksiin mikro-rakenteiden sopeutuksen kautta. Havaitaan, että aggregaativisen tuottavuuskasvun mikrorakennetekijät vähentävät tuottavuuden ja palkojen hajontaa toimipaikkojen välillä. Lamavuosina ulkoinen sopeutuminen toimipaikkasyntymien ja - poistumien kautta ja vähemmässä määrin myös rakennemuutos toimintaansa jatkavien toimipaikkojen keskuudessa on parantanut aggregatiivista suorituskykyä joillakin palvelutoimialoilla. Myös monilla ei-teollisilla toimialoilla toipumisjaksoa luonnehtii hyytyminen.
Keywords: L60; L80; O12; O32; O47; 330; Produktivität; Wirtschaftliche Anpassung; Industrielle Forschung; Verarbeitendes Gewerbe; Finnland